PENGEMBANGAN BAHAN AJAR STRUKTUR ALJABAR BERBASIS PROBLEM SOLVING DENGAN STRATEGI ABDUKTIF-DEDUKTIF - Hamidah Suryani Lukman (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2015)
This paper tells about research and development result that has been aplicated into three steps, preliminary, small group trial, and field test. The preliminary steps included analysis of teaching materials; design and develop the teaching materials based problem solving with abductive-deductive strategy; perform validation by fou expert validator; and do the first revision. The small group trials included product trials to the six randomly selected student; and do the second revision. Single one shot case study research design has been used in this step. The field test included product trials to the 15 students that registered as Abstract Algebra lecturing participant at Mathematics Education Program in Muhammadiyah University of Sukabumi. Before-after research design has been used in this step. The instruments that used in this research are observation sheet, validation sheet, interview guide, students’ response scale, performance assessment sheet of teaching materials, and test of students’ mathematical proof ability. Result of this research showed that teaching materials based problem solving with abductive-deductive strategy is a good category. Effectivity of teaching materials usage evaluated by students’ comprehension speed, students’ interested, students’ creativity, and students’ learning outcomes significantly better than learning effectivity without teaching materials. Effectivity of teaching materials usage evaluated by students’ mathematical proof significantly better than learning effectivity without teaching materials. Therefore, teaching materials based problem solving with abductive-deductive strategy has been valid, practice, and effective to use.